2020
DOI: 10.1097/rli.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

A Deep-Learning Diagnostic Support System for the Detection of COVID-19 Using Chest Radiographs

Abstract: Objectives: The aim of this study was to compare a diagnosis support system to detect COVID-19 pneumonia on chest radiographs (CXRs) against radiologists of various levels of expertise in chest imaging. Materials and Methods: Five publicly available databases comprising normal CXR, confirmed COVID-19 pneumonia cases, and other pneumonias were used. After the harmonization of the data, the training set included 7966 normal cases, 5451 with other pneumonia, and 258 CXRs with COVID-19 pneumonia, whereas in the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
0
35
0
2
Order By: Relevance
“…The system performance was comparable with that of six independent readers. In a more recent study [299], the performance of a newly introduced DL-based system trained on publicly available datasets was compared against 11 radiologists for the three-way discriminatory diagnosis of COVID-19 pneumonia vs. other pneumonias or normal. The system detected COVID-19 very accurately and outperformed radiologists at various training levels, while it was able to separate COVID-19 pneumonia from other types of pneumonia more accurately than were the human readers.…”
Section: Artificial Intelligence In the Diagnosis Of Covidmentioning
confidence: 99%
“…The system performance was comparable with that of six independent readers. In a more recent study [299], the performance of a newly introduced DL-based system trained on publicly available datasets was compared against 11 radiologists for the three-way discriminatory diagnosis of COVID-19 pneumonia vs. other pneumonias or normal. The system detected COVID-19 very accurately and outperformed radiologists at various training levels, while it was able to separate COVID-19 pneumonia from other types of pneumonia more accurately than were the human readers.…”
Section: Artificial Intelligence In the Diagnosis Of Covidmentioning
confidence: 99%
“…However, most of the published studies used relatively small datasets (<1000 CXR images of COVID-19 cases). [40][41][42][43][44] Transfer learning is an ML approach that can help investigators overcome limited data sizes. A CNN is pretrained with results of a previous training round from a different domain.…”
Section: Detection Of Covid-19 On Medical Imagingmentioning
confidence: 99%
“…Deep learning techniques are giving promising results in assessing the radiological features of COVID-19 [61][62][63][64]. In particular, a recent study found that a proposed algorithm reached a significantly higher overall diagnostic accuracy than that obtained by a simple radiologist observation both in COVID-19 pneumonia than in pneumonia from other causes [65].…”
Section: Role Of Hrct In Discriminating Lung Involvement and The Diffusion Of Deep Learning Techniquesmentioning
confidence: 99%